Cable conveying device - XI JIAONA; HU WEIHONG; SUN MINGHUA; FAN JIANHUA; LU WEIGUO; ZHUANG ZHIYANG; ZHOU FEI; WU JIANLIN; SUN YIJIE (2024)
The utility model discloses a cable conveying device, which relates to the technical field of cable production and comprises a double-layer platform and a conveying assembly, the double-layer platform comprises an upper platform and a lower platform, the conveying assembly comprises a conveying frame, a driving part and a cable conveying part, the conveying frame is connected with the upper platform, the driving part is connected with the conveying frame, and the cable conveying part is connected with the driving part; wherein the plurality of pay-off racks are distributed on the upper platform and the lower platform, the driving part drives the cable conveying part to move between the upper platform and the lower platform, and the cable conveying part pulls a cable head of a cable core on the pay-off rack on the upper platform. The cable conveying device provided by the utility model has the effects of improving the space utilization rate of a plant, ensuring the practicability and convenience of lead wires